Clustering Organizational Learning Capability Indices for Knowledge Sharing in Different Segments of the Firm - Masoomeh Alikhani; Hamed Fazlollahtabar; Iraj Mahdavi (International School for Social and Business Studies, 2013)
Since maximization of learning and organizational learning capabilities is the most important element for the success of knowledge management in each organization, this paper focuses on the dimensions of organizational learning capability. We suggest a mathematical clustering structure of dimensions according to their effect on the learning capability for different parts of the organization in order to obtain the highest level of learning capability in an organization. The proposed mathematical clustering aims to relate the needs of different sections of a firm to the corresponding learning capabilities.